RELICTS OF THE PRIMARY MAGMATIC ACCESSORY SPINELS IN THE ARCHEAN KOMATIITES OF THE EASTERN FENNOSCANDIA - Зоя Павловна Рыбникова; Zoya Rybnikova (Proceedings of the Karelian Research Centre of the Russian Academy of Sciences, 2015)
The article presents the results of a complex study of the relicts of the primary magmatic spinels from the Archean (3.0-2.7 Ga) komatiitic series of the greenstone structures of the eastern Fennoscandian Shield. The accessory minerals of the massive and mesocumulate zones of differentiated komatiite flows (containing 24-30 wt. % MgO) are analyzed. The coexistence of several generations of spinels including relicts of the primary magmatic chromite-alumochromite (Cr 2 O 3 44.64-51.80, AI 2 O 3 9.39-13.74, #Cr 68.97-78.52, #Mg 3.98-12.14, #Fe <12), which is an equilibrium mineral phase in komatiitic melts crystallizing in the temperature range of 1340-1370 °C after the extraction of olivine, is established in the komatiites. The identified geochemical zoning in the primary spinels is the result of the equilibrium crystallization of komatiitic melt with a gradual decrease in temperature, which leads to the formation of alumochromite-subferrialumochromite solid solutions. It is shown that the metamorphic transformation of rocks at pressure > 5 kbar and temperatures > 500 °C leads to a complete recrystallization of the primary spinels.